Analisis Kesulitan Mahasiswa dalam Memahami Konsep Teorema Stokes pada Mata Kuliah Kalkulus Vektor - Farhanul Ichsan; Indri Pebrianti; Suci Dahlya Narpila (Lembag, 2025)
This study aims to analyze students’ difficulties in understanding the concept of Stokes’ Theorem in the Vector Calculus course. The method used is a descriptive qualitative approach with data collected through semi-structured interviews with mathematics education students who have studied the topic. The results show that students struggle to comprehend the relationship between line integrals and surface integrals, as well as to connect the concept of curl with vector direction in three-dimensional space. Limited understanding of prerequisite material and the lack of visual media further exacerbate these difficulties. Students reported that learning methods based on visualization and group discussion were helpful. This study recommends the use of contextual learning strategies and interactive media to improve students’ understanding of abstract concepts in Stokes’ Theorem.